Role of medical history in brain tumour development. Results from the international adult brain tumour study - Schlehofer, Brigitte; Wahrendorf, Jürgen (International journal of cancer, 1999)
In an international population-based case-control study carried out in 8 centres in 6 countries, we investigated the role of specific medical conditions in the aetiology of brain tumours in adults. Recruited were 1,178 glioma and 331 meningioma cases and 2,493 age- and gender-matched population controls. Only medical conditions occurring at least 2 years before brain tumour diagnosis were considered. Relative risks (RRs) and 95% confidence intervals (CIs) were estimated using a conditional logistic regression model. Heterogeneity between centres was tested. No association between meningioma and previous medical conditions was observed. For glioma, there was an increased risk associated with epilepsy (RR = 6.55, 95% CI 3.40-12.63), but this was considerably weaker for epilepsy of more than 20 years duration. The risk remained elevated after adjustment for use of anti-epileptic drugs. There was a statistically significant inverse association between glioma and all allergic diseases combined (RR = 0.59, 95% CI 0.49-0.71); this was also observed for specific allergic conditions, namely, asthma and eczema. Subjects who reported a history of infectious diseases (e.g., colds, flu) showed a 30% reduction in risk (RR = 0.72, 95% CI 0.61-0.85). The decreased risks for glioma in subjects reporting a history of allergic conditions or infectious diseases may indicate an influence of immunological factors on the development of glioma. The association between glioma and epilepsy has to be interpreted cautiously and needs further investigation.
Gesehen am 11.02.2019